Stability of timber structures under wind-induced forces A parametric study of stabilizing systems in timber structures - WENNERHOLM, OLIVER; THULIN, WILLIAM (My University, 2023)
The use of timber as a construction material has gained popularity in recent years and is continuously growing due to increased interest in climate neutrality. This is mostly the result of staying in line with the Paris Agreement, but also due to the new legislation from Boverket in 2021 demanding a climate declaration on all newly built structures. However, challenges arise when constructing timber structures due to their limited stiffness and mass compared to concrete buildings of similar geometry. This thesis examines various structural systems commonly employed in timber construction to assess their performance under wind loading, specifically in terms of lateral deformation and wind-induced acceleration. Finite element analysis (FEA) is conducted using a parametric model implemented in Grasshopper with Karamba3d. The objective of this research is to provide engineers with guidance for the preliminary design of the stabilizing system in timber structures. The model was verified with FEM-design. The verified finite element model was used to assess the behavior of timber structures, with particular focus on crosslaminated timber walls, which are currently not supported in Karamba3D. The comparison between the model and FEM-design showed small differences, mostly below 5% and never exceeding 10%. The analysis evaluated wind-induced acceleration according to EKS12 against the comfort demands specified in ISO10137 and ISO6897, while transversal deflection results were compared to the general engineering practice of h/500. The findings demonstrate that both stiffness and mass significantly influence the building’s ability to meet these demands. Mass was found to be particularly important for acceleration, whereas stiffness played a crucial role in deflection control. Among the pure timber concepts examined, with a footprint of 41x21 meters and office building requirements, the design featuring a 320mm timber core with two 990x625mm timber trusses on each side achieved the highest structural height of 35 meters. Additionally, by incorporating a concrete floor slab, it has the potential to reach heights of 63 meters or more.
Keywords: Structural dynamics, Stabilizing system, Timber structures, Wind-induced acceleration, Global deflection, Parametric analysis, Karamba3D, Grasshopper.